Process evaluation of complex interventions: Medical Research Council guidance - Moore, Graham F; Audrey, Suzanne; Barker, Mary; Bond, Lyndal; Bonell, Chris; Hardeman, Wendy; Moore, Laurence; O’Cathain, Alicia; Tinati, Tannaze; Wight, Daniel; Baird, Janis (BMJ (Online), 2015)
Process evaluation is an essential part of designing and testing complex interventions. New MRC guidance provides a framework for conducting and reporting process evaluation studies